Edukasi Pengetahuan Ibu Hamil Dalam Pencegahan Stunting Di Desa Banyumas Kabupaten Langkat Tahun 2025 - Rismaida Saragih; Siti Arfah Siregar (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
Indonesia continues to face a significant burden of stunting that seriously impacts human resource quality and national development. Stunting is defined as a condition of chronic linear growth failure in children under five years, characterized by height-for-age below minus two standard deviations (−2 SD) from the WHO Child Growth Standards median, resulting from prolonged nutritional deficiency during the first 1,000 days of life. Indonesia's national stunting prevalence in 2022 remained at 21.6%, far from the 2024 national target of 14%. This community service activity aimed to improve the knowledge of pregnant mothers and mothers with toddlers regarding the definition, causative factors, impacts, and prevention strategies of stunting in Banyumas Village, Stabat District, Langkat Regency, in 2025. A community-based participatory intervention approach with a pre-post single group design was employed, incorporating interactive health counseling, group discussion sessions, anthropometric examination of toddlers, and pre-test and post-test knowledge assessments using a validated questionnaire. Participants consisted of 21 pregnant mothers and mothers with toddlers, with 7 toddlers undergoing anthropometric examination. Results demonstrated a significant increase in the mean knowledge score from 55.24 (pre-test) to 82.38 (post-test), reflecting an improvement of 27.14 points. Anthropometric examination identified 1 out of 7 toddlers (14.3%) as having poor nutritional status based on the height-for-age index. Beyond measurable knowledge gains, the activity successfully promoted perceptual change among participants, fostered the active role of local health cadres as community change agents, and cultivated collective awareness regarding the importance of multi-stakeholder collaboration in stunting prevention efforts. It is recommended that posyandu cadres actively sustain the 1,000 HPK counseling program on a continuous basis, and that the institution develop more comprehensive follow-up community service programs in the target area.